Inferencing Skill and Attentional Control Account for the Connection Between Reading Comprehension and Mathematics - Kim, Young-Suk Grace (Frontiers in Psychology, 2021)
We examined the relations of inference, vocabulary, decoding, short-term memory, and attentional control to reading comprehension and mathematics performance for first-grade students in the US (N = 83). The students were composed of 75% Hispanics, 15% Whites, and 6% Asian Americans. Students’ performance on mathematics and reading comprehension were very strongly related (r = .88). Results from path analysis showed that inference (.27 ≤ 𝛽s ≤ .38) was independently and positively related to both reading comprehension and mathematics performance after accounting for short-term memory, attentional control, decoding, and vocabulary. Decoding was independently related to reading comprehension, but not mathematics, whereas vocabulary was independently related to mathematics, but not to reading comprehension. Attentional control was directly related to mathematics, and indirectly related to reading comprehension and mathematics via inference, vocabulary, and decoding, with a substantial total effect on reading comprehension and mathematics (.56). Short-term memory was not directly nor indirectly related to reading comprehension and mathematics. Overall these results show that language and cognitive skills are shared resources of reading comprehension and mathematics, and highlight the roles of attentional control and inference skill in reading comprehension and mathematics.